Decreased diabetes risk over 9 year after 18-month oral l-arginine treatment in middle-aged subjects with impaired glucose tolerance and metabolic syndrome (extension evaluation of l-arginine study) - Monti, Lucilla D.; Galluccio, Elena; Villa, Valentina; Fontana, Barbara; Spadoni, Serena; Piatti, Pier Marco (European journal of nutrition, 2018)
Purpose This study aimed to determine whether l -arginine supplementation lasting for 18 months maintained long-lasting effects on diabetes incidence, insulin secretion and sensitivity, oxidative stress, and endothelial function during 108 months among subjects at high risk of developing type 2 diabetes. Methods One hundred and forty-four middle-aged subjects with impaired glucose tolerance and metabolic syndrome were randomized in 2006 to an l -arginine supplementation (6.4 g orally/day) or placebo therapy lasting 18 months. This period was followed by a 90-month follow-up. The primary outcome was a diagnosis of diabetes during the 108 month study period. Secondary outcomes included changes in insulin secretion (proinsulin/c-peptide ratio), insulin sensitivity (IGI/HOMA-IR), oxidative stress (AOPPs), and vascular function. After the 18 month participation, subjects that were still free of diabetes and willing to continue their participation (104 subjects) were further followed until diabetes diagnosis, with a time span of about 9 years from baseline. Results Although results derived from the 18 month of the intervention study demonstrated no differences in the probability of becoming diabetics, at the end of the study, the cumulative incidence of diabetes was of 40.6% in the l -arginine group and of 57.4% in the placebo group. The adjusted HR for diabetes ( l -arginine vs. placebo) was 0.66; 95% CI 0.48, 0.91; p < 0.02). Proinsulin/c-peptide ratio ( p < 0.001), IGI/HOMA-IR ( p < 0.01), and AOPP ( p < 0.05) levels were ameliorated in l -arginine compared to placebo. Conclusions These results may suggest that the administration of l -arginine could delay the development of T2DM for a long period. This effect could be mediated, in some extent, by l -arginine-induced reduction in oxidative stress.